Pregnancy rate in indigenous ewes by direct transfer of vitrified embryos - Ghosh, S; Talukder, MRI; Jha, PK; Alam, MGS; Juyena, NS; Bari, FY (Bangladesh Veterinarian, 2018)
The effects of PMSG on superovulation, quality of embryos, and pregnancy rate were studied following transfer of vitrified embryos into indigenous ewes. Three donor and nine recipient ewes were synchronized using two intramuscular doses of Cloprostenol (PGF2α) equivalent to 125 μg Prostaglandin F2α (Ovoprost® Bayer, New Zealand) at an interval of nine days. To ensure ovulation donor and recipient ewes were treated with 600 iu and 250 iu Pregnant Mare Serum Gonadotrophin (PMSG; Folligon®, Intervet, Boxmeer, The Netherlands) at the time of 2nd injection of Prostaglandin F2α. All donor ewes were mated by fertile rams. Embryos were collected from donor ewes on day six after mating by inguinal laparotomy. Grade 1 embryos were vitrified using standard procedure. After thawing the embryos were transferred into the exteriorized uterine horn of the recipient by inguinal laparotomy. Pregnancy diagnosis was performed by trans-abdominal ultrasonography on Day 40 of transfer. Oestrus occurred 31.3 ± 8.1 hours after second injection of prostaglandin and 32.6 ± 8.7 hours in recipients. Oestrus lasted 24.7 ± 9.9 hours in donors and 32.8 ± 12.8 hours in recipients. The mean numbers of corpora lutea and embryos of donor ewes were 11.7 ± 4.0 and 8 ± 2.6, respectively. Total embryo recovery rate of donor ewes was 68.6%. The mean values of qualities of embryo yield of donor ewes were 6 ± 1.7 grade 1, 0.3 ± 0.6 grade 2, 1.3 ± 1.2 grade 3, and 0.3 ± 0.6 grade 4. Twenty embryos were vitrified, 16 embryos were transferred and four recipient ewes were found pregnant. The pregnancy rate of recipient ewes was 44.4%. Bangl. vet. 2017. Vol. 34, No. 1, 27-33